Dogs as Sentinels for Flavivirus Exposure in Urban, Peri-Urban and Rural Hanoi, Vietnam - Long Pham-Thanh; Thang Nguyen-Tien; Ulf Magnusson; Vuong Bui-Nghia; Anh Bui-Ngoc; Duy Le-Thanh; Åke Lundkvist; Minh Can-Xuan; Thuy Nguyen-Thi Thu; Hau Vu-Thi Bich; Hu Suk Lee; Hung Nguyen-Viet; et al. (Viruses, 2021)
Diseases caused by flaviviruses, including dengue fever and Japanese encephalitis, are major health problems in Vietnam. This cross-sectional study explored the feasibility of domestic dogs as sentinels to better understand risks of mosquito-borne diseases in Hanoi city. A total of 475 dogs serum samples from 221 households in six districts of Hanoi were analyzed by a competitive enzyme-linked immunosorbent assay (cELISA) for antibodies to the pr-E protein of West Nile virus and other flaviviruses due to cross-reactivity. The overall flavivirus seroprevalence in the dog population was 70.7% (95% CI = 66.4–74.8%). At the animal level, significant associations between seropositive dogs and district location, age, breed and keeping practice were determined. At the household level, the major risk factors were rural and peri-urban locations, presence of pigs, coil burning and households without mosquito-borne disease experience (p < 0.05). Mosquito control by using larvicides or electric traps could lower seropositivity, but other measures did not contribute to significant risk mitigation of flavivirus exposure in dogs. These results will support better control of mosquito-borne diseases in Hanoi, and they indicate that dogs can be used as sentinels for flavivirus exposure.